Pengelolaan Desa Wisata Berbasis CBT (Community Based Tourism) di Desa Wisata Sriwulan, Kecamatan Limbangan, Kabupaten Kendal - Fauziah Amalia; Ilyas Ilyas (Departement of Mathematics Education, 2024)
The Sriwulan tourist village is a tourist village that actuate management by involving the community as implementers. This research aims to describe CBT (Community Based Tourism)-based tourism village management, local community participation, as well as supporting and inhibiting factors for CBT-based tourism village management. This research uses a qualitative approach with the research subjects being the manager, Pokdarwis, community and tourists. Data validity techniques use triangulation of sources and methods with data analysis techniques using data collection, reduction, data display and drawing conclusions. The results show that CBT-based management in the Sriwulan tourist village has four stages is planning, organizing, actuating, and controlling. Community participation is seen through participation in decision making, participation in implementation, participation in benefits, and participation in evaluation. Meanwhile, supporting and inhibiting factors for management consist of internal and external factors. In conclusion, all stages of CBT-based management in the Sriwulan tourist village involve the role of the community directly or indirectly. Based on the research results, the suggestions are to expand promotions, increase community empowerment efforts through managerial training for managers and product manufacturing training for the community, as well as improving the infrastructure of the Sriwulan tourist village.